Estimation of Structures Under Ancient Archaeological Sites Site of Jabung Temple, Probolinggo, Indonesia Using Geolistrik Resistivity Method - Kosmas Isdarmadi; Adi Susilo; Sunaryo Sunaryo (Natural B, Journal of Health and Environmental Sciences, 2013)
The sounding of geoelectrical resistivity distribution using dipole-dipole configuration around the Jabung temple site located in the Jabung Candi village, Paiton, Probolinggo District, East Java province, Indonesia has been done by using Resistivitymeter OYO MacOhm. The aim of the research was to determine the distribution and depth of rock below the Jabung temple area also as an information for investigation and discovery efforts of ancient objects which are still burried. Aquisition are taken by ten lines and ±20.042 m2 of coverage area. Line 1, 2, 3, 4, 5, 6 located around in Menara Sudut temple at length of measurement line12 m and at a distance of electrode spacing are 1 m, where lines 1 and 4 located in outcrop of Menara Sudut tample. While lines 7, 8, 9, and 10 located in all area of Jabung temple. Lines 7 and 8 have length of measurement lines 150 m with spacing 10 m, while lines 9 and 10 have length of measurement lines 200 m with spacing 4 m, where line 8 located pass to main Jabung tample. The processing of data was using RES2DINV software. Resistivity values that are used to determine the temple rock is the resistivity value of sandy clay. Base on geoelectrical investigation and interpretation shows the sandy clay as temple rock with resistivity value 33 Ω.m to 92.6 Ω.m on average depth of 1.79 m and the others remain of tample rock around the main Jabung tample. This research shows geoelectrical method is good idea to subsurface sounding especially for archeology case, it caused this method is simple and more cheap than ekskavation method.